2019
DOI: 10.14336/ad.2018.0807
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Staining may be Associated with Intracerebral Hemorrhage but Not Functional Outcome in Acute Ischemic Stroke Patients Treated with Endovascular Thrombectomy

Abstract: To evaluate the incidence of post-interventional contrast staining (PICS) in acute ischemic stroke (AIS) Chinese patients who were treated with endovascular thrombectomy (ET) and investigate potential association of PICS with functional outcome and intracerebral hemorrhage (ICH). This observational study was based on a single-center prospective registry study. AIS patients who underwent ET from January 2013 to February 2017 were recruited into this study. All patients had dual-energy CT (DECT) scan of the head… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 31 publications
(36 reference statements)
1
41
1
Order By: Relevance
“…Phan et al concluded on a series of 42 patients that DECT accurately differentiates between contrast and blood, but that metallic streak and calcifications could lead to identification failure [ 12 ]. This was supported by later studies [ 6 , 7 , 23 ].…”
Section: Reviewsupporting
confidence: 77%
“…Phan et al concluded on a series of 42 patients that DECT accurately differentiates between contrast and blood, but that metallic streak and calcifications could lead to identification failure [ 12 ]. This was supported by later studies [ 6 , 7 , 23 ].…”
Section: Reviewsupporting
confidence: 77%
“…42 However, while contrast staining predicts intracranial hemorrhage, in another study it was not found to be associated with symptomatic hemorrhage or functional outcomes. 35…”
Section: Ischemic Strokementioning
confidence: 99%
“…2,33 Parenchymal high attenuation is often seen immediately post-EVT due to disruption of the blood-brain barrier leading to iodine extravasation which causes contrast staining on CT. Differentiation between contrast staining and acute hemorrhage is difficult in single-energy CT as both appear hyperdense. 34 Dual-energy CT can differentiate parenchymal contrast staining from hemorrhage through generation of iodine overlay maps to isolate iodinated contrast and virtual noncontrast maps to subtract high attenuation due to iodine [34][35][36][37][38][39] (Figure 2). Use of DECT techniques changed the report from intracerebral hemorrhage to contrast staining in 34% of a series of post-EVT patients.…”
Section: Post-thrombectomymentioning
confidence: 99%
See 1 more Smart Citation
“…It always presents as a hyperdensity on computed tomography (CT) imaging and thus is sometimes difficult to distinguish from intracerebral haemorrhage. 1 Previous studies have found that the hyperdense abnormalities detected on post-procedural CT scans may be a result of transitory disruption of the integrity of the blood-brain barrier (BBB), 2 which may be one of the reasons why contrast extravasation is common in patients with acute stroke. Studies have also demonstrated that contrast enhancement following neuroendovascular procedures may be associated with intracranial haemorrhage, consequently leading to poor prognoses in patients with acute ischaemic stroke.…”
Section: Introductionmentioning
confidence: 99%